FAMILY SCATHOPHAGIDAE - Wolff, Marta; Grisales, Diana; Nihei, Silvio S. (Zootaxa, 2016)
Scathophagidae (Diptera, Calyptratae) is an uncommon group of flies. In Colombia there was no scientific record of this family until now. In this paper we report for the first time the genus Scatogera and the species S. primogenita Albuquerque, collected over 3000m. and previously collected in Ecuador.